2016
DOI: 10.1007/s10734-016-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of academic dishonesty in Romanian university students

Abstract: Academic dishonesty in higher education is an increasingly visible problem throughout the world and in Romania in particular. A total of 1127 university students from six public Romanian universities were surveyed for their experiences and beliefs with 22 behaviors that might be considered academically dishonest. A five-factor solution to the High Educ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Since the disciplinary committee protocols were publicly available, female students could potentially become aware of such punishing inequity and it might trigger the neutralizing effect in further occurrences of VAI. Other research (e.g., Ives et al 2017 ) failed to demonstrate gender differences in VAI.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Since the disciplinary committee protocols were publicly available, female students could potentially become aware of such punishing inequity and it might trigger the neutralizing effect in further occurrences of VAI. Other research (e.g., Ives et al 2017 ) failed to demonstrate gender differences in VAI.…”
Section: Introductionmentioning
confidence: 89%
“…VAI involve one of the following four general categories of behavior (which will be discussed in the next section): cheating, plagiarism, fabrication of information, or facilitation of such misconduct (Pavela 1997 ). For instance, in a study of more than a thousand university students in Romania (Ives et al 2017 ), about 95% reported having engaged in one or more VAI. This phenomenon continues to preoccupy researchers and educators in the hopes of reaching a greater understanding of its determinants and of finding effective methods of reducing its scope.…”
Section: Introductionmentioning
confidence: 99%
“…In Romania there are several studies that have shown high levels of acceptance of cheating and plagiarism among students (e.g. Ives et al, 2017). Recently, the Ministry of Education and Research (Order of the Ministry of National Education No.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, the legacy of a relatively high level of instruction took some time to wear off. It was not until the 2000s that stagnation or decline became obvious to even domestic observers (The Economist, August 7th, 2012; Ives et al, 2017;Abbott, 2011Abbott, , 2012. Second, government and education officials worked hard to project an image of success in Western-type education, both at home and abroad (Tomusk, 2000).…”
Section: Introductionmentioning
confidence: 99%